PEMAKNAAN MOTIF TOKEK PADA KAIN TENUN UTAN WELAK MAUMERE - Feri Sanjaya (FISIP Universitas Bung Karno, 2020)
Abstract Indonesia is known as a civilized nation. Including one of them the work of Maumere ikat. The cloth comes from Flores, which has high artistic value and is beautiful. In general, woven ikat maumere fabric is fabric made from weaving processes that require so much energy and time. Maumere ikat is also made by women who have high creativity and artistic creations. Maumere's ikat weaving is not only limited to artistic creations, but its making also considers symbols of social, religious, cultural and economic status. Even certain motifs are made through high concentration of thought. This research is related to the meaning of motifs in Welak Maumere Ikat Weaving cloth with Gecko motifs. The meaning of the